The Price of a Neglected Zoonosis: Case-Control Study to Estimate Healthcare Utilization Costs of Human Brucellosis. - Oded Vered; Tzahit Simon-Tuval; Pablo Yagupsky; Miki Malul; Assi Cicurel; Nadav Davidovitch (PLoS ONE)
Human brucellosis has reemerged as a serious public health threat to the Bedouin population of southern Israel in recent years. Little is known about its economic implications derived from elevated healthcare utilization (HCU). Our objective was to estimate the HCU costs associated with human brucellosis from the insurer perspective. A case-control retrospective study was conducted among Clalit Health Services (CHS) enrollees. Brucellosis cases were defined as individuals that were diagnosed with brucellosis at the Clinical Microbiology Laboratory of Soroka University Medical Center in the 2010-2012 period (n = 470). Control subjects were randomly selected and matched 1:3 by age, sex, clinic, and primary physician (n = 1,410). HCU data, demographic characteristics and comorbidities were obtained from CHS computerized database. Mean±SD age of the brucellosis cases was 26.6±17.6 years. 63% were male and 85% were Bedouins. No significant difference in Charlson comorbidity index was found between brucellosis cases and controls (0.41 vs. 0.45, respectively, P = 0.391). Before diagnosis (baseline), the average total annual HCU cost of brucellosis cases was slightly yet significantly higher than that of the control group ($439 vs. $382, P<0.05), however, no significant differences were found at baseline in the predominant components of HCU, i.e. hospitalizations, diagnostic procedures, and medications. At the year following diagnosis, the average total annual HCU costs of brucellosis cases was significantly higher than that of controls ($1,327 vs. $380, respectively, P<0.001). Most of the difference stems from 7.9 times higher hospitalization costs (p<0.001). Additional elevated costs were 3.6 times higher laboratory tests (P<0.001), 2.8 times higher emergency room visits (P<0.001), 1.8 times higher medication (P<0.001) and 1.3 times higher diagnostic procedures (P<0.001). We conclude that human brucellosis is associated with elevated HCU costs. Considering these results in cost-effective analyses may be crucial for both reducing health inequities and optimal allocation of health systems' scarce resources.